2018
DOI: 10.2147/ott.s180505
|View full text |Cite
|
Sign up to set email alerts
|

The elevated glutaminolysis of bladder cancer and T cells in a simulated tumor microenvironment contributes to the up-regulation of PD-L1 expression by interferon-γ

Abstract: BackgroundMetabolic reprogramming occurs in the tumor microenvironment and influences the survival and function of tumor and immune cells. Interferon-γ (IFN-γ) produced by T cells up-regulates PD-L1 expression in tumors. However, reports regarding the relationship between nutrient metabolism and the up-regulation of PD-L1 expression are lacking.Materials and methodsIn this paper, we analyzed the metabolic changes in T cells and bladder cancer cells in a simulated tumor microenvironment to provide evidence rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Therefore, Tiam1 in tumor cells may be an attractive therapeutic target. Fourth, increasing evidence showed that the stromal microenvironment within cancers is a pivotal factor of regulating the growth, invasiveness, and metastasis and chemo-sensitivity of cancer cells, [64][65][66][67][68] and Tiam1 expressed in tumor stromal microenvironment also plays a role in regulating tumor invasion, metastasis and chemo-resistance. CAF is a major stromal cell in cancer stromal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Tiam1 in tumor cells may be an attractive therapeutic target. Fourth, increasing evidence showed that the stromal microenvironment within cancers is a pivotal factor of regulating the growth, invasiveness, and metastasis and chemo-sensitivity of cancer cells, [64][65][66][67][68] and Tiam1 expressed in tumor stromal microenvironment also plays a role in regulating tumor invasion, metastasis and chemo-resistance. CAF is a major stromal cell in cancer stromal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells also have a degree of metabolic plasticity in response to limiting glucose availability. For instance, when glucose levels are low, effector T cells have the ability to adapt and increase glutamine uptake and glutaminolysis to support cellular metabolism [224]. However, in conditions of severe cellular ATP depletion, the nutrient-sensor AMPK becomes activated and induces a catabolic program to preserve survival of immune cells.…”
Section: Metabolic Adaption Of Immune Cells In Inflammatory Microenvimentioning
confidence: 99%
“…Here, for the first time, we identified the direct involvement of Chk-α in immunosupression, as Chk-α downregulation significantly increased PD-L1 levels. Chk-α downregulation also shifted cancer cells towards a more immunosuppressive profile through metabolic reprogramming, increasing the production of metabolites such as lactate [ 12 ], glutamate [ 14 ], MTA [ 60 ], or glutamine [ 61 ], which have been linked to increased immune resistance of cancer cells. In a recent study, lower lactate production by cancer cells led to lower in vivo extracellular lactate and improved functioning of T cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…High glycolysis and lactate production [ 8 , 9 ], glutamine deprivation [ 10 ], and changes in the redox state [ 11 ] have been shown to influence the TIME. PD-L1 levels are, furthermore, directly modulated in cancer cells by lactate [ 12 ], arginine [ 13 ], or glutamate [ 14 ], and in immune cells by arginine [ 13 ] and glutamine [ 15 ]. As a result, metabolic inhibitors of the glutamate, glutamine, and arginine pathways are being evaluated in clinical trials in combination with immune checkpoint inhibitors with promising outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%